The Influence of Product Quality, Brand Image and Word of Mouth on the Interest in Repurchasing Scarlett Whitening Body Lotion Products in Jakarta National University Students - Nadia Nadia; Resti Hardini; Kumba Digdowiseiso (Jurnal Syntax Admiration, 2023)
The purpose of this study was to analyze whether there was an effect of Product Quality, Brand image, and Word of mouth on the Repurchase Interest of Scarlett whitening Body lotion products in students at the National University of Jakarta. The data used in this research is using primary data. The data collection technique was carried out using a questionnaire obtained by distributing questionnaires via google form to 96 National University students. The data analysis technique used in this research is multiple linear regression analysis, which is processed through the SPSS version 25 program. The data analysis technique used is a quantitative method where the results are expressed by numbers. Based on the results of research that has been done, it shows that product quality has a positive and significant effect on repurchase intention, brand image has a positive and significant effect on repurchase interest, word of mouth has a positive and significant effect on repurchase interest.